PHYSICAL AND CHEMICAL PROPERTIES OF THE EPIDOTE MINERALS- AN INTRODUCTION- - Franz G.; Liebscher A. (My University, 2004)
Epidote minerals are known since the 18th century, but at that time the greenish to dark colored varieties were termed actinolite or schorl and not distinguished from the minerals to which these names apply today. Haüy deﬁ ned the mineral species and introduced the name “epidote” in 1801, whereas Werner in 1805 used the term pistacite (quoted from Hintze 1897). Epidote is derived from greek epidosis = to increase, because the base of the rhombohedral prism has one side larger than the other and pistacite refers to its green color (all references for names after Lüschen 1979; Blackburn and Dennen 1997). Weinschenk (1896) proposed the name clinozoisite from its monoclinic symmetry and zoisite-like composition for those monoclinic members of the epidote family that are Fe poor, optically positive and have low refractive indices and birefringence.
Keywords: Epidote